Interventional treatments and risk factors in patients born with hypoplastic left heart syndrome in England and Wales from 2000 to 2015. Issue 18 (25th January 2018) - Rogers, Libby; Pagel, Christina; Sullivan, Ian D; Mustafa, Muhammed; Tsang, Victor; Utley, Martin; Bull, Catherine; Franklin, Rodney C; Brown, Kate L
Abstract : Objective: To describe the long-term outcomes, treatment pathways and risk factors for patients diagnosed with hypoplastic left heart syndrome (HLHS) in England and Wales. Methods: The UK's national audit database captures every procedure undertaken for congenital heart disease and updated life status for resident patients in England and Wales. Patients with HLHS born between 2000 and 2015 were identified using codes from the International Paediatric and Congenital Cardiac Code. Results: There were 976 patients with HLHS. Of these, 9.6% had a prepathway intervention, 89.5% underwent a traditional pathway of staged palliation and 6.4% of infants underwent a hybrid pathway. Patients undergoing prepathway procedures or the hybrid pathway were more complex, exhibiting higher rates of prematurity and acquired comorbidity. Prepathway intervention was associated with the highest in-hospital mortality (34.0%). 44.6% of patients had an off-pathway procedure after their primary procedure, most frequently stenting or dilation of residual or recoarctation and most commonly occurring between stage 1 and stage 2. The survival rate at 1 year and 5 years was 60.7% (95% CI 57.5 to 63.7) and 56.3% (95% CI 53.0 to 59.5), respectively. Patients with an antenatal diagnosis (multivariable HR (MHR) 1.63 (95% CI 1.12 to 2.38)), low weight (<2.5 kg) (MHR 1.49 (95% CI 1.05 to 2.11)) or the presence of an acquired comorbidity (MHR 2.04 (95% CI 1.30 to 3.19)) were less likely to survive. Conclusion: Treatment pathways among patients with HLHS are complex and variable. It is essential that the long-term outcomes of conditions like HLHS that require serial interventions are studied to provide a fuller picture and to inform quality assurance and improvement.